Analysis Scientific Approach Effect On Mathematical Communication Ability Of Junior High School Students - Ratna Apriyani; Usman Aripin ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2022)
This research is classroom action research. This research aims to analyze the effect of the scientific approach on students' mathematical communication. The method used is descriptive qualitative. The subjects of this study were 34 students of class VII SMP Pasundan 3 Cimahi, consisting of 22 male students and 12 female students. The test instrument used in this study was in the form of a test in the form of a description of 5 questions using indicators of students' mathematical communication skills on comparative material and a non-test used in the form of a questionnaire on the learning activity attitude scale as many as 20 positive and negative questions. This research was carried out in 2 cycles consisting of 2 meetings in each cycle. The data analysis technique used in this study was carried out in three stages, 1) data reduction, 2) data presentation, and 3) conclusion stage. The results of students' answers are shown by the N-Gain data in the Average category with a score of 0,4381. The results of data analysis show that there is an influence of a scientific approach on students' mathematical communication skills after being given action of 70%. Therefore, it can be concluded that there is an effect of using a scientific approach on mathematical communication skills.